Application of RFLP-PCR-Based Identification for Sand Fly Surveillance in an Area Endemic for Kala-Azar in Mymensingh, Bangladesh - Mohammad Shafiul Alam; Hirotomo Kato; Mizuho Fukushige; Yukiko Wagatsuma; Makoto Itoh (Journal of Parasitology Research)
Mymensingh is the most endemic district for kala-azar in Bangladesh. Phlebotomus argentipes remains the only known vector although a number of sand fly species are prevalent in this area. Genotyping of sand flies distributed in a VL endemic area was developed by a PCR and restriction-fragment-length polymorphism (RFLP) of 18S rRNA gene of sand fly species. Using the RFLP-PCR analysis with AfaI and HinfI restriction enzymes, P. argentipes, P. papatasi, and Sergentomyia species could be identified. Among 1,055 female sand flies successfully analyzed for the species identification individually, 64.4% flies was classified as Sergentomyia species, whereas 35.6% was identified as P. argentipes and no P. papatasi was found. Although infection of Leishmania within the sand flies was individually examined targeting leishmanial minicircle DNA, none of the 1,055 sand flies examined were positive for Leishmania infection. The RFLP-PCR could be useful tools for taxonomic identification and Leishmania infection monitoring in endemic areas of Bangladesh.